Adopting e-commerce in a family-owned SME distribution company in the automotive post-warranty after-sales service spare parts market: Vokshyenn Trading Sdn Bhd - Khong, Yi Wane (2020)
The study is about a small and medium-enterprise adopting e-Commerce in the automotive post-warranty after-sales service spare parts market. Vokshyenn Trading Sdn Bhd (Vokshyenn) is a Malaysian SME family owned spare parts import wholesale distribution currently facing stiff competition in the market and is looking to adopt e-Commerce to improve its competitiveness and sales growth.